2023
DOI: 10.1111/eea.13282
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the microbial community in fall armyworm Spodoptera frugiperda during a life cycle

Abstract: The fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), is a destructive pest that causes serious damage worldwide, particularly to maize cultivars. The microbiota of S. frugiperda might play a role in its development and adaptability to different environments. However, the dynamics of microbial communities in S. frugiperda during its life cycle remain poorly understood. In this study, we used the amplification of the 16S rRNA gene to characterize the microbiome of all developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…37,38 Furthermore, gut microbe composition is highly variable among individuals due to effects of diet and other environmental factors, 39 even changing across developmental stages. 29,40 Following infection by HearNPV, specific microbiota in the larval midgut underwent proliferation in parallel with virus replication, although most others declined in abundance. However, the microbial increase in midgut tissues, without contents, was relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Furthermore, gut microbe composition is highly variable among individuals due to effects of diet and other environmental factors, 39 even changing across developmental stages. 29,40 Following infection by HearNPV, specific microbiota in the larval midgut underwent proliferation in parallel with virus replication, although most others declined in abundance. However, the microbial increase in midgut tissues, without contents, was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to clarify the influence of microbiota on viral infection can be confounded by antibiotic treatments used to produce axenic larvae, as these can vary in their efficacy in clearing the bacterial community, sometimes causing dysbiosis, mitochondrial dysfunction, and even toxicity to the host 37,38 . Furthermore, gut microbe composition is highly variable among individuals due to effects of diet and other environmental factors, 39 even changing across developmental stages 29,40 . Following infection by HearNPV, specific microbiota in the larval midgut underwent proliferation in parallel with virus replication, although most others declined in abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that MIL-101-SL, CF-SC, and CF@MIL-101-SL affect digestive function and inhibit S. frugiperda growth by altering the relative abundance of species associated with nutrient and energy availability, and the influence was greater with H–CF@MIL-101-SL treatment. Chen et al reported a high pathogenicity of Stenotrophomonas in S. frugiperda.…”
Section: Resultsmentioning
confidence: 99%
“…h i b i t e d .species associated with nutrient and energy availability, and the influence was greater with H−CF@MIL-101-SL treatment. Chen et al51 reported a high pathogenicity of Stenotrophomonas in S. frugiperda. The relative abundance of Stenotrophomonas was increased with MIL-101-SL, CF-SC, and CF@MIL-101-SL treatments, which resulted in reduced resistance of S. frugiperda and promoted pathogen invasion.…”
mentioning
confidence: 99%
“…Chen et al (2023) used 16S rRNA amplification sequencing to characterize the microbiome of fall armyworm larvae, pupae, and adults. They found that the bacterial diversity of young larvae was highest, and overall, Proteobacteria and Firmicutes were most abundant.…”
Section: This Special Issuementioning
confidence: 99%